A study of cervical cytology in females above 21 years of age - Singh, Nidhi; Gehlot, Hanslata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cancer cervix is the leading cause of mortality and morbidity in developing countries like India most probably due to lack of proper screening facilities or due to the lack of awareness amongst the women of developing countries. Worldwide, cervical cancer is the second most common and 5th deadliest cancer in women. This study was conducted in department of obstetrics and Gynaecology, Umaid hospital, Dr. S. N. Medical College, Jodhpur Rajasthan, India. The objective of this study was to study the various high risk factors involved in premalignant and malignant lesions of cervix. To study the incidence of different epithelial abnormalities of cervix in females above 21 years of age. To study premalignant and malignant lesions of the cervix in relation to the presenting complaint Methods: The study was conducted in 500 females above 21 years of age and who were not pregnant, who had been attending Umaid Hospital, Jodhpur for various gynaecological complaints, of different parity, residential status and socioeconomic class. Detailed history was taken and thorough examination was done. Pap smear was prepared and all smears were reported as per the Bethesda system. Results: Maximum numbers of patients were in the age group of 21-40 years (70.2%). Majority of patients were from rural area (52.4%) and from lower socioeconomic class (30.2%). Most of women were found to have duration of marriage between 10 to 30 years (63.4%). Most of the women in our study had age at marriage between 17 to 19 years (49.4%). Multiparity was seen in 84.2% of cases. The commonest presenting complaint was white discharge (46.8%). On Pap smear, maximum cases were of inflammatory smear (91.4%), 1.4% had ASCUS, 1.2% AGC, 1.4% LSIL, 1% HSIL and 0.4% had SCC. Conclusions: Cervical cytology is an important tool for early detection of premalignant and malignant lesions of cervix. Regular pap smear screening should be conducted in vulnerable age groups.